Using agent-based adaptive learning environments for knowledge sharing management. (2015) - Palomino, Cecilia Estela Giuffra; Silveira, Ricardo Azambuja; Nakayama, Marina Keiko
This paper describes how an intelligent or adaptive learning management systems (LMSs) based on multiagent systems is useful and effective for knowledge sharing engineering or management. A complete model of intelligent learning environment based on intelligent tutoring systems (ITSs) using software agents is described, and a prototype based on this model was designed and constructed using the Moodle LMS as a case study. The proposed adaptive model takes into account how the users use to access the subject matter resources and how much can be perceived that they succeed on activities proposed by the knowledge engineer. The agents interact with the users by sending messages to them, and manage the knowledge sharing by changing the resources and activities available by the knowledge engineer. Thus, the agents perform the actions previously defined by the knowledge engineer, in a personalised and adaptive way according to each user's personal way of learning.